The Effect of Play Therapy on Children’s Anxiety in Hospitalization : Literature Review - Muhamad Khusnul Maab; Tenang Aristina; Nunung Rachmawati; Yayang Harigustian (UrbanGreen, 2021)
Background: Hospitalization is a process for planning or emergency reasons that requires the child to be treated or stay in the hospital for treatment which can cause some changes in the child's psyche. They will face an unfamiliar environment, unfamiliar staff such as doctors and nurses and disruption to their lifestyle. The impact of hospitalization is the anxiety experienced by the child as a result of nursing actions if not treated immediately it will cause the child to refuse to get further nursing action. Methods: The design used in identifying the research carried out was by means of a literature review. Search articles using Google Scholar and Pubmed. Results: The results described from the three studies conducted showed negative results, namely the effect of play therapy on children's anxiety. Conclusion: Most of the respondents experienced a high level of anxiety before playing therapy and after playing therapy in children undergoing hospitalization, the level of anxiety in children decreased.